Fourth International Conference on Advances in Social Science, Economics and Management Study - SEM 2016 2016
DOI: 10.15224/978-1-63248-094-1-54
|View full text |Cite
|
Sign up to set email alerts
|

Work Engagement among Women Engineers in Malaysia

Abstract: This research aims to examine the effects of Effort-Reward Imbalance on work engagement among women engineers in Malaysia. In this study we review the Effort-Reward Imbalance (ERI) model as the psychosocial work environment that consisted of three distinct dimensions, namely effort, reward and over-commitment. In this study, a total of 300 questionnaires were distributed to women engineers, but only 250 questionnaires have been completed by the respondents. The data were analyzed using correlation and multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…It means that the supervisor's support, task orientation, and physical conditions in the organization help the employees feel energetic while performing their work. This result is congruent with previous research which also showed a significant positive association between the work environment and work engagement in the corporate sector (Ashari et al, 2016) and hospitality sector (Suan and Nasruddin, 2016). Even though it is only at a moderate strength, this relationship is strong enough to claim the existence of the relationship between the work environment and work engagement.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…It means that the supervisor's support, task orientation, and physical conditions in the organization help the employees feel energetic while performing their work. This result is congruent with previous research which also showed a significant positive association between the work environment and work engagement in the corporate sector (Ashari et al, 2016) and hospitality sector (Suan and Nasruddin, 2016). Even though it is only at a moderate strength, this relationship is strong enough to claim the existence of the relationship between the work environment and work engagement.…”
supporting
confidence: 92%
“…For instance, the role of supervisor support is to support the effort of employees in the organization to improve performance and create a supportive environment in the organization. Similarly, Ashari et al (2016) found that the work environment and work engagement possessed a positive relationship. This is because a good relationship among employees increases the level of work engagement in the organization.…”
Section: Relationship Between Work Environment and Work Engagementmentioning
confidence: 92%